SUMMARY: SOME FACTORS RELATED TO TREATMENT COMPLIANCE OF PATIENTS WITH TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the factors related to treatment adherence of patients with type 2 diabetes at My Xuyen District’s Medical Center. Subjects and methods: Study of description and analysis of the relationship between factors and adherence to treatment of diabetes on 385 medical records of diabetes at the Center My Xuyen District’s Medical Center, from November 2019 to March 2020. Results: Male patients complied well with the rate of 75.2%, while that of female patients was only 69.0%. The compliance rate of patients >70 years old was high at 81.3%, the lowest compliance rate was in the group of patients